Analysis and design of algorithms - Rajput, Vinod Kumar (S.K. Kataria & Sons, 2012)
This book provides an exhaustive and comprehensive treatment of designing procedure of algorithms and how to analyze algorithms. It is intended primarily for use in undergraduate and postgraduate cources in data structures and algorithms.